Improving High School Students’ Ability to Write Procedural Text Through Project-Based Learning - Basong, Emilius; Pariyanto, Pariyanto (Sintuwu Maroso Journal of English Teaching, 2024)
The overall goal of this research is enhancing student learning outcomes in process text writing is the goal of this study. In the interim, the particular goals of this study are to: (1 )enhance the project-based learning model's application of learning procedure text; (2 )surmount the challenges encountered during the execution of procedure text learning; and (3 )the efforts required of teachers to surmount challenges during procedure text learning. Action research conducted in classrooms using a project-based learning methodology was used in this study. Class XI IPS students at SMAN 1 Sintang make up the population in this study. Samples of 19 female and 16 male students are included. This research uses a test instrument consisting of a description test to collect data and an assessment rubric that is in accordance with the procedure text. Drawing conclusions from the findings of this study, the following can be said: There are 4 students in the satisfactory group (12% )out of 35 students, 12 fall into the fair group (34% ), and 19 fall into the good category (54% ). By applying the project-based learning model to procedural text material, it has been proven to improve students' writing skills in just two cycles.